Knowledge worker tasks in system architecture - Pańkowska, Małgorzata (Zadania pracownika wiedzy w architekturze systemowej, 2019)
In this paper, knowledge workers are assumed to actively realize knowledge management tasks. They are involved in the gathering, analysis, storage and dissemination of knowledge in a way that is focused on its improvement. Therefore main goal is to present system architecture models for knowledge management in information science domain. In that domain, Design Science Research (DSR) is discussed as being very useful and adopted in this paper for knowledge management. The author applied the ArchiMate modelling language and supplemented it with the process approach and Business Process Model & Notation (BPMN) for knowledge management process presentation, as well as by the case management approach and Case Management Model & Notation (CMMN). These notations are consistent and complementary, although they have different objectives of usage
Informatyka Ekonomiczna = Business Informatics, 2019, Nr 1 (51), s. 55-71
Keywords: system architecture; cyber-ethnography; ArchiMate; Design Science Research; BPMN; CMMN; architektura korporacyjna; architektura systemowa; cyberetnografia